Alcohol sponsorship and its impact on sports participants' consumption. Issue 7 (3rd July 2017) - Kelly, Sarah; Ireland, Michael; Mangan, John
Abstract: The aim of this study was to examine the association between alcohol consumption, alcohol sponsorship in sports and preferences of sponsored sportspeople regarding sponsorships/consumption. We investigate the impact of alcohol sponsorship on sportspeople in the Australian population using a national survey of sportspeople ( N  = 2367), representing a range of club and professional sports. The results show an association between alcohol sponsorship of sport and increased alcohol consumption among sports participants (i.e. 'sportspeople'). Additionally, a preference for sponsored alcohol brands was found by sponsored sportspeople. Our research adds to the growing evidence for policy review of alcohol sponsorship of sports and extends prior studies investigating impacts of alcohol sponsorship upon sports participants by generalizing to a large, national sample of sportspeople.